Triangulation of needs analysis in English for tourism purposes - Tonić, Aleksandar (Vestnik za tuje jezike, 2010)
The article presents the results of my research in English for Tourism Purposes, a branch of English Language Teaching which is still relatively underdeveloped and which, in Slovenia, has been rather scarcely researched and studied. The base for the research is triangulation, the latest procedure used in the planning and realization of needs analyses. It is more reliable than informal cross-checking as it makes use of multiple sources and/or methods of acquiring information. The research thus outlines an overview of the basics of English for Specific Purposes, illustrating and stressing the use of triangulation, which has never before been used in similar Slovenian researches. Learners, teachers and domain experts are the sources used; methods are questionnaire and interview. In conclusion, the importance of using triangulation in Needs Analysis is commented upon, the reliability of study results is substantiated and grounds for further studies in English for Tourism Purposes in Slovenia are set.
Keywords: angleščina; English; strokovni jezik; analiza potreb; triangulacija; turizem; tourism